2017
DOI: 10.1016/j.ajic.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Workplace interventions associated with influenza vaccination coverage among health care personnel in ambulatory care settings during the 2013-2014 and 2014-2015 influenza seasons

Abstract: Background Vaccination of health care personnel (HCP) can reduce influenza-related morbidity and mortality among HCP and their patients. The objective of this study was to investigate workplace policies associated with higher influenza vaccination coverage among HCP who worked in ambulatory care settings without influenza vaccination requirements. Methods Data were obtained from non-probability Internet panel surveys of HCP conducted in April 2014 and April 2015. Respondents were asked about vaccination stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…A study conducted in the US showed that vaccination coverage among HCWs, who reported at least two interventions, was about twice than HCWs without any intervention at the workplace [29]. These results were similar to those shown by a recent review on interventions to increase influenza vaccination coverage among HCWs, which reported that vaccination uptake had a direct relation with multiple intervention strategies adopted in health care settings [30][31][32].…”
Section: Discussionsupporting
confidence: 77%
“…A study conducted in the US showed that vaccination coverage among HCWs, who reported at least two interventions, was about twice than HCWs without any intervention at the workplace [29]. These results were similar to those shown by a recent review on interventions to increase influenza vaccination coverage among HCWs, which reported that vaccination uptake had a direct relation with multiple intervention strategies adopted in health care settings [30][31][32].…”
Section: Discussionsupporting
confidence: 77%
“…A study conducted in US showed that vaccination coverage among HCWs who reported at least two workplace interventions was about twice than HCWs without any intervention at workplace [28]. These results were similar to others of recent review articles on interventions to increase influenza vaccination coverage among HCWs which reported that vaccination uptake increases with an increasing number of intervention program in health care settings [29,30].…”
Section: Discussionsupporting
confidence: 79%
“…Institutional informative and communicative strategies at the UH of Palermo contributed to a substantial increase in vaccination coverage. Only with an adequate information and a better university training, false perceptions on influenza vaccination could be modified over time [28].…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, all the initiatives and strategies adopted in healthcare contexts to improve influenza vaccination knowledge, attitudes, and perceptions could contribute to an increase in adherence [ 37 , 38 , 39 , 40 ]. Palermo UH adopted several strategies in previous seasons that contributed to a reduction in vaccine hesitancy and considerably increased vaccination adherence among HCWs [ 9 ].…”
Section: Discussionmentioning
confidence: 99%